2014
DOI: 10.1111/ahg.12085
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Polymorphisms in a Sodium Channel GeneSCN7Aand Essential Hypertension: A Case-Control Study in the Northern Han Chinese

Abstract: SummaryNa x , an α-subunit of the sodium channel encoded by the SCN7A gene, has been deemed to be a sensor of the concentration of sodium in the brain and may be involved in salt intake behavior. We inferred that Na x /SCN7A may participate in the regulation of blood pressure and the pathogenesis of essential hypertension (EH). The present case-control study involving 615 hypertensives and 617 normotensives was performed to investigate the association between SCN7A polymorphisms and EH in the Northern Han Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…3B) (23). Highly divergent genes in this pathway are mainly involved in ion transport (SCN7A, SLC9A1, ATP1A4, and CACNA2D4), which is important for myocardial function (24). We also found strong signals of adaptation in two major adrenergic receptors (ADRA1A and ADRA2B), as previously reported (7).…”
Section: Adaptive Changes In Other Cardiovascular Genessupporting
confidence: 86%
“…3B) (23). Highly divergent genes in this pathway are mainly involved in ion transport (SCN7A, SLC9A1, ATP1A4, and CACNA2D4), which is important for myocardial function (24). We also found strong signals of adaptation in two major adrenergic receptors (ADRA1A and ADRA2B), as previously reported (7).…”
Section: Adaptive Changes In Other Cardiovascular Genessupporting
confidence: 86%
“…Na x is considered to fulfill the criteria of brain [Na + ] sensor because it detects small increases in extracellular [Na + ] (Hiyama et al, 2002(Hiyama et al, , 2013. Of note, a recent epidemiological study suggested that polymorphisms in the SCN7A gene encoding Na x were associated with ''essential hypertension'' (Zhang et al, 2015). Collectively, these findings support our view that information on [Na + ] increases in body fluids sensed by Na x in the OVLT is used for BP control.…”
Section: Discussionmentioning
confidence: 57%
“…3d). The GCs specifically express two of the voltage gated channels, Kcnj5 and Scn7a , which are both linked to hypertension 27,28 (Fig. 3h, i).…”
Section: Resultsmentioning
confidence: 99%